Auranofin, identified by FDA-approved drug library screening, inhibits HBs antigen secretion via lysosomal damage - Akiyoshi Shimoda; Kazuhiro Murai; Hayato Hikita; Satoshi Minami; Takayuki Miyake; Shinji Kuriki; Emi Sometani; Jihyun Sung; Satoshi Shigeno; Yuichiro Higuchi; Kazuki Maesaka; Kumiko Shirai; et al. (PLoS ONE, 2026)
Background and aim Hepatitis B surface antigen (HBsAg) is associated with hepatocellular carcinoma risk and immune exhaustion and contributes to hepatitis B virus (HBV) persistence. Current anti-HBV treatments have a limited ability to reduce HBsAg levels. This study aimed to identify FDA-approved drugs capable of reducing HBsAg levels and explore the underlying mechanisms. Methods A total of 1134 FDA-approved compounds were screened at 9.9 μM for 7 days using HepG2.2.15.7 cells, which contain an integrated HBV genome. HBsAg in the supernatant and cell viability were assessed. Compounds whose viability was reduced by >1 SD were excluded. Compounds whose HBsAg concentration decreased by >1.5 SD were selected and validated at 0.5 and 5 μM. We evaluated the HBsAg-reducing effect of the final candidate compounds using HBV-infected primary human hepatocytes (HepaSH cells) derived from chimeric TK-NOG mice and investigated the underlying mechanism responsible for the reduction in HBsAg. Results After 126 cytotoxic compounds were excluded, the HBsAg levels of the 6 candidates decreased by >1.5 SD. Ethacridine and auranofin significantly reduced the level of HBsAg at both 5 and 0.5 μM. In HepaSH cells, only auranofin decreased the level of HBsAg. Auranofin did not affect the HBe antigen, HBV-DNA, or pregenomic RNA, nor did it reduce the level of intracellular HBsAg, as determined by Western blotting. Transmission electron microscopy revealed more vesicles in auranofin-treated HepaSH cells than in control cells. Immunofluorescence analysis of HepaSH cells treated with auranofin revealed increased Galectin-3 expression and colocalization of HBsAg with Galectin-3, which was consistent with lysosomal damage, compared with those of the untreated controls. Conclusion Auranofin, an FDA-approved antirheumatic agent, reduces HBsAg secretion via lysosomal damage.